2006
DOI: 10.1245/aso.2006.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Mesothelioma Treated by Cytoreductive Surgery and Intraperitoneal Hyperthermic Chemotherapy: Results of a Prospective Study

Abstract: A therapeutic strategy combining cytoreductive surgery with HIPEC seems to provide an adequate and efficient locoregional treatment for peritoneal mesothelioma. It is associated with acceptable morbidity when performed by an experienced surgical team. The completeness of cytoreduction is the major determinant of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 36 publications
6
68
0
1
Order By: Relevance
“…Recently, however, several independent phase Ⅰ/Ⅱ prospective trials have reported improved survival with an intensive loco-regional treatment strategy, including cytoreductive surger y along with perioperative intraperitoneal chemotherapy in the form of hyperthermic intraperitoneal chemotherapy, with or without early postoperative intraperitoneal chemotherapy [23] . The median survival after aggressive surgery combined with hyperthermic intraperitoneal chemotherapy has approached 5 years and seems to improve with subsequent reports [22,23,[26][27][28] . Meanwhile, Vogelzang et al [29] have demonstrated in a multicenter, controlled, randomized phase Ⅲ trial that pemetrexed-cisplatin is the gold standard for the non-operable malignant pleural mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, several independent phase Ⅰ/Ⅱ prospective trials have reported improved survival with an intensive loco-regional treatment strategy, including cytoreductive surger y along with perioperative intraperitoneal chemotherapy in the form of hyperthermic intraperitoneal chemotherapy, with or without early postoperative intraperitoneal chemotherapy [23] . The median survival after aggressive surgery combined with hyperthermic intraperitoneal chemotherapy has approached 5 years and seems to improve with subsequent reports [22,23,[26][27][28] . Meanwhile, Vogelzang et al [29] have demonstrated in a multicenter, controlled, randomized phase Ⅲ trial that pemetrexed-cisplatin is the gold standard for the non-operable malignant pleural mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…For low-grade tumors CC-0 and CC-1 cytoreductions are considered complete cytoreductive operations. The completeness of cytoreduction score is the most significant prognostic indicator of survival in patients with pseudomyxoma peritonei (Sugarbaker, 2006;Miner et al, 2005;Baratti et al, 2007) peritoneal mesothelioma (Yan et al 2007;Sebbag et al, 2000;Brigand et al, 2006;Deraco et al, 2006), colorectal cancer with peritoneal carcinomatosis Gomez-Portilla et al, 1999) gastric cancer with peritoneal carcinomatosis (Yonemura et al, 2003), and peritoneal sarcomatosis (Rossi et al, 2004;Berthet et al, 1999). The completeness of cytoreduction score in advanced ovarian cancer has been demonstrated to be a significant prognostic indicator of survival Tentes et al, 2006;Piso et al, 2004;Raspagliesi et al, 2006;Di Giorgio et al, 2008 (Tentes et al, 2006).…”
Section: Completeness Of Cytoreduction Scorementioning
confidence: 99%
“…In particular, while CRS reduces the tumoral mass (an optimal cytoreduction aims to residual disease smaller than 2,5mm), HIPEC maximizes loco-regional chemotherapy cytotoxicity while limiting the systemic side effects (Vlasveld et al, 1991;Markman, 1990;Markman and Kelsen, 1992). In this perspective, some encouraging experiences in numerous centers demonstrated a median survival of 40 to 90 months and a 5-ys-OS of 30 to 60% (Yan et al, 2007;Brigand et al, 2006;Deraco et al, 2006;Feldman et al, 2003;Loggie et al, 2001;Nonaka et al, 2005;Park et al, 1999;Sugarbaker et al, 2003). All peritonetomy center agree that complete cytoreduction is the prognostic principal factor for clinical success and that complete cytoreduction is correlated to the initial extent of intrabdominal disease and to the ability of the surgical team.…”
Section: Advanced Oncological Surgery In Malignant Peritoneal Mesothementioning
confidence: 99%